Media Attention and Deliberation on the Supreme Court. (June 2023) - Badas, Alex; Justus, Billy
The news media acts as a "watchdog" over political institutions by holding them accountable for their actions through critical commentary. Being that the Supreme Court rarely interacts directly with the public, the news media is the primary mechanism through which individuals become aware of the Supreme Court's actions and decisions. Thus, for the Supreme Court, the news media's role as a "watchdog" takes greater meaning than it does for institutions that often speak directly to the public. Considering this, along with the Supreme Court's use of strategic presentation, we argue that news media attention to particular cases will influence the extent to which the Supreme Court deliberates on argued cases. We find support for our hypothesis in four contexts. First, cases with more news media attention take longer to produce a published opinion. Second, cases with greater media attention are more likely to be reargued. Third, cases with more news media attention produce a higher number of draft opinions before being published. Fourth, cases with more news media attention produce opinions with a greater share of cognitive mechanisms included in them. Our results have implications for the Justice's use of strategic behavior and the potential constraints faced by the Court in its decision-making.